Clinical dilemma and systemic treatment strategy of triple-negative breast cancer in the elderly - CHEN Junyao, ZHANG Wentao, LIU Qiao, NIE Jianyun (Zhongguo aizheng zazhi, 2023)
There is no specific biomarker for triple-negative breast cancer (TNBC), and chemotherapy remains as backbone but with limited efficacy and more side effects. 10%-21% TNBC are elderly patients with high prevalence of concomitant cardio-cerebrovascular and renal complications, which may lead to intolerance of chemotherapy. How to properly treat these elderly TNBC patients becomes a big challenge during daily clinical practice. To date, few clinical trials specifically focus on elderly TNBC patients, thus no enough evidence-based safety and efficacy data are provided to support the proper therapy to this population. There are also challenges and controversies in the diagnosis and treatment. Elderly TNBC patients have special age-related disease characteristics and high non-cancer related mortality. Therefore, it is very important to balance survival benefit and quality of life during the treatment. This paper summarized data of the epidemiology, tumor biological behavior, current diagnosis and treatment status and the huge unmet medical needs of elderly TNBC patients, and explored the benefits of novel antibody-drug conjugate (ADC), to provide certain guidance on systemic treatment strategies for elderly TNBC patients.